PENATALAKSANAAN FISIOTERAPI PADA KASUS BRONCHOPNEUMONIA (A CASE REPORT) - Brina Wendita Dwiarindi, (Journal of Innovation Research and Knowledge, 2022)
Introduction: Bronchopneumonia is an acute infection of the lower respiratory tract in the lungs, which anatomically affects the lung lobules starting from the lung parenchyma to the border of the bronchi which can be caused by bacteria, viruses, fungi and foreign bodies. Characterized by shortness of breath, nasal flaring, and cyanosis (discoloration) around the nose or mouth. The effort that can be given is to give a nebulizer (inhalation) which is a treatment by administering drugs. Meanwhile, chest physiotherapy (chest physical therapy) is an intervention to help free a blocked airway caused by mucus/secretions. Methods: This research uses a case study research method. Results: At T1: (5) to T4: (3) as well as an increase in the ability to expel sputum. Conclusion: Based on the research description and discussion above that there is a decrease in shortness of breath and an increase in the ability to expel sputum during 4 treatments. Keywords: Bronchopneumonia, nebulizer, chest physical Therapy.